1993
DOI: 10.1007/bf02012149
|View full text |Cite
|
Sign up to set email alerts
|

Carpal and tarsal osteolysis: An MRI, angiographic and histopathologic study

Abstract: The case of a 13-year-old girl with striking carpal and tarsal osteolysis (sporadic occurrence) is reported. MRI confirmed the total absence of carpal bones and medial tarsal bones. Dense fibrocollagenous tissue replaced the spaces left by the resorbed bones. Arteriography showed occlusion of the radial artery at the level of the physis of the distal radius with increased tortuosity of the ulnar artery. There was no major vascular occlusion in the foot except for some indistinct and blurred tarsal branches of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 8 publications
1
12
0
1
Order By: Relevance
“…The Torg patient reported by Eisenstein et al [1998] was noted to have a "coarse facial appearance" and high arched palate and epicanthal folds. Frontal bossing, hypertelorism, micrognathia, and mental retardation were seen in a patient with carpal and tarsal osteolysis and plantar subcutaneous nodules reported by Choi et al [1993]. Facial changes, specifically maxillary hypoplasia and relative exopthalmos, also have been reported in autosomal dominant forms with [Carnevale et al, 1985;Kohler, 1973] and without nephropathy [DeSmet, 1980;Thieffry and SorrelDejerine, 1958].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The Torg patient reported by Eisenstein et al [1998] was noted to have a "coarse facial appearance" and high arched palate and epicanthal folds. Frontal bossing, hypertelorism, micrognathia, and mental retardation were seen in a patient with carpal and tarsal osteolysis and plantar subcutaneous nodules reported by Choi et al [1993]. Facial changes, specifically maxillary hypoplasia and relative exopthalmos, also have been reported in autosomal dominant forms with [Carnevale et al, 1985;Kohler, 1973] and without nephropathy [DeSmet, 1980;Thieffry and SorrelDejerine, 1958].…”
Section: Discussionmentioning
confidence: 91%
“…The nodules reported by Torg et al [1969] in two of the three affected sibs were nontender nodules found near the knees, feet, and elbows and on top of the interphalangeal joints with hyperpigmented and erythematous bases. A thumb-tip size nontender, firm subcutaneous nodule was present in the left sole of a 13-year-old patient with carpal, tarsal osteolysis syndrome [Choi et al, 1993]. Biopsy of the tissue that replaced the space left by the resorbed carpal bones showed irregularly arranged dense fibrous collagenous tissue with no definite evidence of inflammation or vascular proliferation.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, there were three other papers prior to 1991, i.e., Carnevalle et al [7], who reported one family (three patients) with ICTO type I and one patient with type III; Castells et al [16] and Rocco et al [17] described two cases with sporadic disease. After 1991, two families (five patients) with ICTO type I [18, 19] and ten patients with type III [9,10,13,[20][21][22][23][24][25][26] were reported. To our knowledge, 15 families (46 patients) with ICTO type I, three families (10 patients) with type II and 42 patients (including our patients) with type III have been reported to date.…”
Section: Discussionmentioning
confidence: 99%
“…Nephropathy has been reported in association with ICTO (Tables 2, 3). Only a few reports have described the renal histopathological aspects, particularly in the early course of the nephropathy [9][10][11][12][13][14]. Renal involvement is more severe and occurs more frequently in type III and is usually associated with hypertension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation